Cochlear implantation via middle fossa approach – a case report. (4th July 2019) - Mankekar, Gauri; Arriaga, Moises A.; Viator, Dori; Volk, Jerome M.
Abstract : Objective: Cochlear implantation is routinely performed all over the world via the post-auricular, facial recess approach. Our case study describes the middle fossa approach for the management of bilateral profound sensorineural hearing loss in a female child with multiple external, middle and inner ear malformations. The middle fossa approach has been reported sporadically and has been used inconsistently in patients with chronic otitis media and inner ear malformations. Case study: A 3-year-old female child presented with bilateral profound sensorineural hearing loss, bilateral anotia, right cochlear nerve agenesis, right facial paralysis, bilateral mild inner ear dysplasia and an aberrant left facial nerve covering the left round window. Further tests indicated that she was a suitable candidate for cochlear implantation and was medically cleared for surgery. In view of the multiple malformations and high risk of injury to her only functioning left facial nerve on the side with a cochlear nerve, cochlear implantation via a middle fossa approach was performed. Conclusion: Middle fossa approach to cochlear implantation is challenging but can be safely performed even in children and offers an option in patients when a routine mastoidectomy, facial recess and round window approach cannot be undertaken.